Bundling Messages to Reduce the Cost of Tree-Based Broadcast Algorithms - Rodrigues, Luiz; Duarte Jr., Elias; de Araujo, João Paulo; Arantes, Luciana; Sens, Pierre (Anais do Latin-American Symposium on Dependable Computing (LADC), 2018)
Hierarchical broadcast strategies based on trees are scalable since they distribute the workload among processes and disseminate messages in parallel. In this work we propose an efficient best-effort broadcast algorithm that employs multiple spanning trees to propagate messages that are bundled on tree intersections. The algorithm is autonomic in the sense that it employs dynamic trees rooted at the source process and which rebuild themselves after processes crash. Experimental results obtained with simulation are presented showing the performance to the algorithm in terms of the latency and the number and sizes of messages employed.